급성중독 응급실 환자에서 Zolpidem 검출과 농도: 일개 중독분석실 229명 사례 - 유재형; Jaehyung Yu; 장한석; Hanseok Chang; 원신애; Sinae Won; 염정훈; Jeonghun Yeom; 이아름; Arum Lee; 박나연; Na-youn Park; et al. (대한임상독성학회지, 2019)
Purpose: Non-benzodiazepine hypnotic drugs (including zolpidem) are associated with an increased risk of suicide and suicidal ideation. Considering the wide usage of zolpidem, this drug should be considered a possible etiology for stupor or coma in any patient exposed to this drug. However, there are no reports on zolpidem blood levels in emergency department patients in Korea. We therefore reviewed the analyzed data of a toxicology laboratory at one university affiliated hospital. Methods: The sex, age, chief symptoms, suspiciousness of poisoning, and presumption of poison were analyzed from January 2018 to June 2019. The detection frequency and level of zolpidem in the patient blood were compared to the mental changes presented, which is the main consequence of zolpidem. Results: A total of 229 toxicological analyses, requested to a toxicological laboratory at one university affiliated hospital, were reviewed. Among 229 patients, the mean age was 54.3±20.7 years old with 113 women and 116 men. 8.7% of patients have psychiatric illness and 39.7% were poisoned intentionally. The chief symptoms detected were: mental change 55.0%, gastrointestinal 14.4%, cardiovascular 10.5%, focal neurological 7.4%, respiratory 3.5%, none 8.7%, and unknown 0.4%. A request for detailed reports revealed that causative poisons were specified only in 20.1% cases. Zolpidem was detected in 22.3% cases (51/229), with median blood level 1.26 mg/L (interquartile 0.1, 5.06 mg/L) and urine 0.90 mg/L (interquartile 0.11, 5.6 mg/L). Furthermore, zolpidem was more frequently detected in toxicology analysis of patients where mental change was the primary symptom, as compared to other symptoms (32.5% vs. 9.7%, p<0.01). Conclusion: This study reported the blood level of zolpidem in suspected poisoning patients admitted to the emergency department.